Effectiveness and usability of the system for assessment and intervention of frailty for community-dwelling pre-frail older adults: A pilot study - Tan, Ren Siang; Goh, Eileen Fabia; Wang, Di; Chan, Robin Chung Leung; Zeng, Zhiwei; Yeo, Audrey; Pek, Kalene; Kua, Joanne; Wong, Wei Chin; Shen, Zhiqi; Lim, Wee Shiong (Frontiers in Medicine, 2022)
Background: Effective multicomponent interventions in the community targeted at preventing frailty in at-risk older adults can promote healthy ageing. However, there is a lack of studies exploring the effectiveness of technology-enabled autonomous multi-domain community-based interventions for frailty. We developed a novel end-to-end System for Assessment and Intervention of Frailty (SAIF) with exercise, nutrition and polypharmacy components. This pilot study aimed to explore SAIF’s effectiveness in improving frailty status, physical performance and strength, and its usability in pre-frail older adults. Methods: This is a single arm 8-week pilot study in 20 community-dwelling older adults who were pre-frail, defined using the Clinical Frailty Scale (CFS) as CFS 3+ (CFS 3 and FRAIL positive) or CFS 4. For outcomes, we assessed frailty status using the modified Fried Frailty Phenotype (FFP) and CFS; physical performance using Short Physical Performance Battery (SPPB); and Hand Grip Strength (HGS) at baseline and 8-week. User experience was explored using the System Usability Scale (SUS), interest-enjoyment subscale of the Intrinsic Motivation Inventory and open-ended questions. We analyzed effectiveness using repeated-measures tests on pre-post scores, and usability using a convergent mixed-method approach via thematic analysis of open-ended responses and descriptive statistics of usability/interest-enjoyment scales. Results: Sixteen participants (71.8±5.5 years) completed the 8-week study. There was a significant improvement in FFP score (-0.5, p<.05, effect size, r=0.43), but not CFS (-1.0, p=.10, r=0.29). Five (31.3%) improved in frailty status for both FFP and CFS. SPPB (+1.0, p<.05, r=0.42) and HGS (+3.5, p<.05, r=0.45) showed significant improvements. Three themes were identified: “Difficulty in module navigation” (barriers for SAIF interaction); “User engagement by gamification” (facilitators that encourage participation); and “Perceived benefits to physical health” (subjective improvements in physical well-being), which corroborated with SUS (68/100) and interest-enjoyment (3.9/5.0) scores. Taken together, user experience results cohere with the Senior Technology Acceptance and Adoption Model. Conclusion: Our pilot study provides preliminary evidence for the effectiveness of SAIF in improving frailty status, physical performance and strength of pre-frail older adults, and offers user experience insights to plan the follow-up large-scale randomized controlled trial.